(untitled) (Global Journal of Medical Research, 2023)
The dancing rules for couples are leading is the male partner who start dancing with the left leg and leads in clockwise direction Why Nonlinear physics teaches that vortices spin clockwise and suck energy If so the spinning clockwise dancing man will suck energy and gain energy from the dance spinning especially in fast spinning waltz The energy gained from the clockwise-spinning dance will be added to the energy from the clockwise spinning of man s aura The total gained energy will be shared with the dancing partner My long-term studies found that the aura is nonlinear electromagnetic field NEMF If so aura energy gain can happen only if there is a reservoir of NEMF energy from which the man can suck NEMF energy in